Severe bronchial asthma requiring ventilation. A review of 20 cases and advice on management. Issue 641 (March 1979) - Webb, A. K.; Bilton, A. H.; Hanson, G. C.
Abstract : The natural history and outcome of 20 asthmatics who required mechanical ventilation is reviewed. Seven of these patients died. The majority of the deaths could have been prevented if: (1) The patient had been followed-up in an asthma clinic and had been fully informed of the danger of an asthmatic attack. (2) The medical staff had been trained more fully in the evaluation and management of a severe asthma attack. Careful sequential assessment will enable timely transfer of patients with severe bronchial asthma to a unit experienced in their management.